2017
DOI: 10.1038/s41598-017-14999-1
|View full text |Cite
|
Sign up to set email alerts
|

Shape representation modulating the effect of motion on visual search performance

Abstract: The effect of motion on visual search has been extensively investigated, but that of uniform linear motion of display on search performance for tasks with different target–distractor shape representations has been rarely explored. The present study conducted three visual search experiments. In Experiments 1 and 2, participants finished two search tasks that differed in target–distractor shape representations under static and dynamic conditions. Two tasks with clear and blurred stimuli were performed in Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…This could be attributed to the motion blur effect generated on the screen and the resource-limited theory of visual cognition. In the research environment of this experiment, the yellow stimuli that moved across the screen had a limited size, and a motion blur effect occurred whenever the speed was too high [32,41]; this increased the difficulty in perceiving movement speed for participants, especially when dealing with small sizes. Moreover, for small-sized stimuli moving at fast speeds, participants may have needed additional saccades to track them during motion, which consumes more cognitive resources.…”
Section: Discussion Of Experiments Imentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the motion blur effect generated on the screen and the resource-limited theory of visual cognition. In the research environment of this experiment, the yellow stimuli that moved across the screen had a limited size, and a motion blur effect occurred whenever the speed was too high [32,41]; this increased the difficulty in perceiving movement speed for participants, especially when dealing with small sizes. Moreover, for small-sized stimuli moving at fast speeds, participants may have needed additional saccades to track them during motion, which consumes more cognitive resources.…”
Section: Discussion Of Experiments Imentioning
confidence: 99%
“…These sizes were chosen based on previous research recommendations for moving objects in maps or interfaces [31]. A Landolt Ring is commonly used in dynamic vision studies [23,32] and adheres to ISO 8596 standards for their inner-to-outer ring ratio. Figure 1 provides specific details, showing the image background as pure black and the target object as uniformly yellow.…”
Section: Methods Of Experiments I 21 Designmentioning
confidence: 99%
“…60 Moreover, due to the target and the distractor had a higher profile similarity. The motion blur caused by the increase in velocity could amplify the shape difference between the contours, 17 thereby reducing the difficulty of searching and finally manifesting as a decrease in once fixation duration. In addition, although the increase in velocity had increased the difficulty of the experiment, our study did not find that participants used passive strategies to search.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the motion velocity, 10 motion direction, motion form, 11–13 and spatial location 14 of the target interferer have an impact on the efficiency and accuracy of human visual search, and these elements are called spatiotemporal attributes of the image. In addition, the surface feature attributes of the image, such as the color, 15 density, 16 and shape of the target/interferer similarity 17 . Also, they have an impact on the efficiency and accuracy of human visual search.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation